Clinical and Radiological Profile and Early Outcome of Skull Base Surgeries in a Tertiary Care Center in Eastern Nepal - Kafle, Prakash; Yadav, Dipak Kumar; Khanal, Babita; Joshi, Narendra Prasad; Sharma, Mohan Raj (Nepal Journal of Neuroscience, 2022)
Background: Surgery of the skull base is challenging due to its complex anatomy and relative inaccessibility. Surgical anatomy and approaches to the cranial base have been well described in the neurosurgical literature.Method: This is an analytical observational study consecutively treated from November 2019 to October 2021 at Nobel medical college teaching hospital, Biratnagar, Nepal. Clinical, radiological, intraoperative ad outcome data were retrieved through the chart review and prospectively collected computer database of the neurosurgery department. The outcome was accessed using mRS. Data was analyzed using Statistical Package for the Social Sciences (SPSS) 25th version. Mean, median, percentage were analyzed.  Chi-squared test was used to find out association between two populations for categorical variables. Logistic regression analysis was used to analyze preoperative selected variables and outcome.  Outcome was assessed at discharge and in six months.Results: A total of 61 cases were included in the study. There was a female preponderance in 73.8%.  The mean age of the study population was 48.5 years. Headache was the most common presenting feature (45.9%) followed by loss of consciousness (21.3%). In the present study, 33(54%) had aneurysms, and 25(40.9%) had brain tumors. The most common approach was anterolateral 67.2% The most common complication observed was hydrocephalus (8.1%).  The median duration of hospital stay was 12 days. The obese patients had significantly longer hospital stays (15 days). At discharge, a favorable outcome (mRS grade ≤ 2) was observed in 83.6%. The preoperative Glasgow coma scale (GCS) was significantly associated with the outcome.Conclusion: Proper pre-operative evaluation and selection of appropriate approaches for the particular patients are key to achieving a good outcome in skull base surgery. The outcome is directly related to preoperative GCS and obese patients tend to have a longer hospital stay.